2022
DOI: 10.1097/iae.0000000000003299
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Correlation of Microvascular Changes on Optical Coherence Tomography Angiography With Retinal Sensitivity in Diabetic Retinopathy

Abstract: Purpose: To assess global, zonal, and local correlations between vessel density changes measured by optical coherence tomography angiography and retinal sensitivity measured by microperimetry across diabetic retinopathy severity. Methods: Diabetic patients and nondiabetic controls underwent optical coherence tomography angiography imaging and microperimetry testing. Pearson's correlation was used to assess associations between average sensitivity and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Capillary nonperfusion is an important feature of DR. VLD and VPD can be used as an indicator to observe the changes in DR capillary perfusion, and the changes in the macula vascular are sensitive indicators for the observation of DR. 5 , 15 This study found that compared with the control healthy group, both VLD and VPD in NPDR patients decreased, suggesting that OCTA is a feasible and effective method to detect DR microvascular disease. 6 Our results were consistent with previous report that retinal blood flow, and blood flow rate of diabetes mellitus (DM) patients were lower than those of normal people, and the diameter of blood vessels in the retinal blood vessels of patients with NDR and NPDR was narrower than normal people.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Capillary nonperfusion is an important feature of DR. VLD and VPD can be used as an indicator to observe the changes in DR capillary perfusion, and the changes in the macula vascular are sensitive indicators for the observation of DR. 5 , 15 This study found that compared with the control healthy group, both VLD and VPD in NPDR patients decreased, suggesting that OCTA is a feasible and effective method to detect DR microvascular disease. 6 Our results were consistent with previous report that retinal blood flow, and blood flow rate of diabetes mellitus (DM) patients were lower than those of normal people, and the diameter of blood vessels in the retinal blood vessels of patients with NDR and NPDR was narrower than normal people.…”
Section: Discussionmentioning
confidence: 65%
“…Optical coherence tomography (OCTA) can show macular vascular morphology quickly and non-invasively in real time. 5 , 6 In addition, OCTA is not affected by traditional contrast fluorescein leakage and masking and drug allergy. Previous study showed that FAZ enlargement was significantly different between diabetic eyes and healthy eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Levine and colleagues performed a detailed point-by-point co-localization to evaluate the correlations between the focal retinal sensitivities and the microvascular changes. They reported that significant correlations were only present in eyes with proliferative diabetic retinopathy 80. Interestingly, Mokrane et al81 reported that areas with retinal sensitivity less than 25 dB were always associated with capillary loss, but some areas of capillary loss had a preserved retinal sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the macular function assessed by MP combined with structural OCT angiography (OCTA) metrics and capillary dropout areas showed low sensitivities in eyes with ischemic DME 8. In addition, the retinal sensitivity determined by MP and the vascular density of both the superficial and deep capillary plexuses determined by OCTA were both significantly correlated with the stage of diabetic retinopathy (DR) 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation